Morphology, physical, and mechanical properties of particleboard made from rape straw and wood particles glued with urea-formaldehyde resin - Cosereanu, Camelia; Cerbu, Camelia (BioResources, 2019)
The morphology, physical, and mechanical properties were investigated for single-layer particleboard made with various proportional contents of wood and rape stalk particles glued with urea-formaldehyde resin. Fine crushed rape stalk particles were used for the experimental particleboards. The weight ratios of rape-to-wood particles were 0:100, 10:90, 30:70, 50:50, and 70:30. Mixed beech and spruce wood particles with percentages of 30% for beech wood and 70% for spruce wood were considered for the configuration. Urea-formaldehyde resin with a solid content of 66 +/- 1% was added to the single-mat configuration at a level of 12%, based on the weight of the particles. Physical (density, water absorption, and thickness swelling) and mechanical (modulus of elasticity, bending strength, internal bond strength) investigations on the particleboards obtained in the laboratory conditions were conducted. The results were compared to the requirements of the EN 312 (2004) standard. In addition, morphological observation at macro- and micro-scale and vertical density profile analysis was conducted on particleboards in order to characterize the interaction between woodrape particles and resin. Variations of the structure and density were observed relative to thickness, providing information concerning to the internal bond performance of the panels.
Keywords: Particleboard; Rape stalk; Wood particles; Physical properties; Mechanical properties; Strength